Answer:
b = -6
Step-by-step explanation:
Apply the exponent rule that
In this case, ![\frac{1}{y^{24}} = y^{-24}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7By%5E%7B24%7D%7D%20%20%3D%20y%5E%7B-24%7D)
Set that equal to
:
![(y^{b})^{4} = y^{-24}](https://tex.z-dn.net/?f=%28y%5E%7Bb%7D%29%5E%7B4%7D%20%3D%20y%5E%7B-24%7D)
Apply the exponent rule that
so now you get:
![y^{4b} = y^{-24}](https://tex.z-dn.net/?f=y%5E%7B4b%7D%20%3D%20y%5E%7B-24%7D)
Since the base is y for both sides of the equation, just set the exponents equal to each other and solve for b.
4b = -24
divide each side by 4 to get:
b = -6
If the annual rate in 10 years has the same quadralaterical value the answer would be 47.9 but we can make sure our answer is correct
what we know:
The cost changed in 10 years to 23.95
if the cost changed another 10 years it would be another 23.95, 23.95+23.95=47.9 Which is our answer pls mark brainliest
Apply substitution
x+4(-2x-4)=19
x – 8x – 16 = 19
-7x = 19 + 16
-7x = 35
x = -5
Then substitute this value to the other equation
y=-2x-4
y = -2(-5) – 4
y = 10 – 4
y = 6
the answer is then letter A. (-5,6)
A solution to a system of equations is a set of values for the variable that satisfy all the equations simultaneously. In order to solve a system of equations, one must find all the sets of values of the variables that constitutes solutions of the system.